Methodological choices for the clinical development of medical devices - Bernard A (Dove Medical Press, 2014)
Alain Bernard,1 Michel Vaneau,2 Isabelle Fournel,3 Hubert Galmiche,2 Patrice Nony,4,5 Jean Michel Dubernard6 1Department of Thoracic Surgery CHU Bocage, Dijon, France; 2Department for Assessment of Medical Devices, HAS (French National Authority of Health), Saint-Denis La Plaine, France; 3Centre of Epidemiology of the Populations, Burgundy University, Dijon, France; 4Department of Clinical Pharmacology, Lyon University CNRS, Lyon, France; 5Laboratory of Biometry and Biology, CNRS, Lyon, France; 6HAS Board (French National Authority of Health), Saint-Denis La Plaine, France Abstract: Clinical evidence available for the assessment of medical devices (MDs) is frequently insufficient. New MDs should be subjected to high quality clinical studies to demonstrate their benefit to patients. The randomized controlled trial (RCT) is the study design reaching the highest level of evidence in order to demonstrate the efficacy of a new MD. However, the clinical context of some MDs makes it difficult to carry out a conventional RCT. The objectives of this review are to present problems related to conducting conventional RCTs and to identify other experimental designs, their limitations, and their applications. A systematic literature search was conducted for the period January 2000 to July 2012 by searching medical bibliographic databases. Problems related to conducting conventional RCTs of MDs were identified: timing the assessment, eligible population and recruitment, acceptability, blinding, choice of comparator group, and learning curve. Other types of experimental designs have been described. Zelen's design trials and randomized consent design trials facilitate the recruitment of patients, but can cause ethical problems to arise. Expertise-based RCTs involve randomization to a team that specializes in a given intervention. Sometimes, the feasibility of an expertise-based randomized trial may be greater than that of a conventional trial. Cross-over trials reduce the number of patients, but are not applicable when a learning curve is required. Sequential trials have the advantage of allowing a trial to be stopped early depending on the results of first inclusions, but they require an independent committee. Bayesian methods combine existing information with information from the ongoing trial. These methods are particularly useful in situations where the number of subjects is small. The disadvantage is the risk of including erroneous prior information. Other types of experimental designs exist when conventional trials cannot always be applied to the clinical development of MDs. Keywords: medical device, randomized controlled trials, assessment, clinical development